IMPROVING THE PEDAGOGICAL COMPETENCE OF MADRASA’S TEACHERS THROUGH A HIGH QUALITY OF TRAINING - Agustina Agustina (Jurnal Dialog, 2018)
English In line with this, this research then aimed to evaluate the training programs and whether or not the trainings had effect on the teachers’ pedagogical competence. To collect the data, this study used a questionnaire and a test to measure the pedagogical competence. The questionnaire was distributed to 104 teachers at MORA Training Institute in Palembang. Some findings showed that the implementation of teachers’ training by the committee was in “good” category, but the aspect of curriculum and syllabus was in “not good” category; the trainers’ roles in the learning process was in “very good” category; the teachers’ pedagogical competence before and after the training significantly improved but the indicator of students’ potential development was in less good category. This study suggested that the curriculum designer should improve the quality of curriculum based on teachers’ needs and take into account the students’ potential development for the training materials. Indonesia Penelitian ini bertujuan untuk mengevaluasi implementasi program diklat guru madrasah dan dampaknya terhadap kompetensi pedagogik guru, menggunakan metode studi kasus terhadap 104 guru pada Balai Diklat Keagamaan Palembang dengan instrumen kuisioner, test pengetahuan pedagogik dan observasi performa pedagogik. Hasil penelitian menunjukkan bahwa implementasi diklat guru dari aspek penyelenggara dinilai baik namun salah satu indikatornya yaitu kualitas kurikulum dan silabus (kursil) dinilai kurang baik; implementasi diklat guru dari aspek widyaiswara dinilai sangat baik; kompetensi pedagogik guru pasca diklat dilihat dari praktik mengajar dinilai baik namun satu indikatornya yaitu pengembangan potensi peserta didik kurang baik dan terdapat peningkatan pengetahuan pedagogik guru pasca diklat seperti yang ditunjukkan pada uji T dari pre dan post test. Direkomendasikan pada para pengembang kurikulum diklat guru untuk meningkatkan kualitas kursil sesuai dengan kebutuhan guru dan memberikan penekanan substansi pengembangan potensi peserta didik dalam diklat-diklat teknis substantif pendidikan.